Combination of the Certainty of Response Index (CRI) and Multiple Choice Tests to Know the Level Misconception of Student in the Human Reproductive System Material - Nasution, Rian Abdillah; Khairuna, Khairuna (Universitas Labuhanbatu, 2022)
The misconception is an error in understanding a concept. Where this misconception shows that there is a difference in the meaning that students understand about a concept that is different from scientific concepts. This study aims to examine the level of misconceptions in the material of the human reproductive system second class-XI of the Senior High School MAN Pematangsiantar which was conducted on April 13-21. This study uses descriptive quantitative methods with diagnostic tests in the form of multiple-choice tests with a combination of Certainty of Response Index and interviews as research instruments by testing to 92 students as samples. The results of this study found that in the reproductive system material, students understand concepts by 54.3%, for misconceptions by 33.9% and for not understand concepts by 11.9%. The highest concept understanding is in the reproductive system disorders material, which is 94.5%, the highest misconception is in the Reproductive System Disorders material at 80.4%, and the highest concept is not understanding the hormone material in menstruation at 25%. Misconceptions that occur due to several things such as lack of learning duration, lack of student interest, boring media and teaching materials, bad study habits. This is the cause of misconceptions at Senior High School of MAN Pematangsiantar so that the overall average is 33.9% which is included in the category of moderate misconceptions.Keywords: CRI, Don't Understand Concepts, Misconception, Human Reproductive System, Understand Concepts